Correlation between BISAP score and D-dimer level on their predictive ability to determine the severity of acute pancreatitis at 24-hours of hospital admission: an observational study - Maitra, Sanjay; Angel Ivy Toppo; Suchitra Pal; Bhabani Chanda Maitra; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2023)
Background: Early prediction of severity of acute pancreatitis (AP) is important for management of AP patients with escalation of care and aggressive therapy which can reduce complications. Bedside index of severity in AP (BISAP) score is helpful in early diagnosis of severe AP. D-dimer, a biomarker of secondary fibrinolysis may be helpful in predicting the severity of pancreatitis. Aims and Objectives: The objective of this study was to evaluate the two scoring systems - the BISAP score and D-dimer in early prediction (within 24 h) on the severity of AP and to analyze how D-dimer correlates with BISAP score. Materials and Methods: Seventy-five patients, aged 18–70 years, suffering from AP due to any cause were included for this prospective, observational study. Within 24 h of admission D-dimer was estimated and BISAP score was calculated. The severity was assessed based on D-dimer level and BISAP scoring systems within 24 h of hospital admission and data were tabulated for analysis. The D-dimer level >2.5 mg/L was considered to be suggestive of severe pancreatitis. The BISAP score >2 in first 24 h was defined as predictive of severe pancreatitis. Spearman rank correlation was used for an analysis of the association between two set of data (BISAP scores and d-dimer levels) and thus to measure the strength and direction of the relationship between the two variables. Results: In the present study, 37.3% of the patients had D-dimer ≤2.5 mg/L and 62.7% had D-dimer>2.5 mg/L’ on calculating the Pearson’s correlation on the ranked values of the data (BISAP scores and D-dimer levels), the correlation coefficient (Spearman’s Rho, designated as “rs”) was found to be 0.406 which indicates about moderate positive correlation. Conclusion: D-dimer testing can be used as an alternative test to predict the severity of AP. It shows a moderate correlation with BISAP scoring.